Childfree As A Women's Right To Freedom In An Islamic Perspective - Rifana, Yulistya; Amelia, Elma; Karier, Moch Andiva Nafidial; Ananta, Maysa Wima (Universitas Nahdlatul Ulama Sunan Giri, 2024)
Marriage is a sacred bond. However, currently, there are still many marriages carried out by underage couples (early marriage). Early marriage has more negative impacts on the psychology of the couple or the affected child, one of which is deciding to choose child-free. Some of the reasons for childfree include medical conditions in the form of disorders or diseases, satisfying professions, and ecological reasons behind the decision of a husband and wife not to have children. The relationship between couples must complement each other, understand each other, and should not feel that their roles are at a higher level between the two. Thus, both must obtain their rights to enjoy an intimate bond (sexual relations). The recommendation to reproduce must be accompanied by full awareness of the responsibility as parents, as stated in the word of Allah SWT in QS Al-Baqarah verse 187. Most Islamic scholars think that children are not the right of the husband or wife alone because children are a shared right between couples. Therefore, to conceive, couples must consider it. Childless couples must take into account various dangers and protect themselves from unexpected events because it eliminates the general assumption of women and abuses the law because it does not match the standards of Islamic Law/Indonesian Sharia Law. The social aspect of having children is essential because we cannot live alone.